A Molecular Model of High Density Lipoproteins - Assmann, Gerd (1974)
Based on the analysis of recombined lipidapoprotein complexes by C-13 and P-31 nuclear magnetic resonance spectroscopy and circular dichroism [Assmann, G., Sokoloski, E. A. & Brewer, H. B., Jr. (1974) Proc. Nat. Acad. Sci. USA 71, 549-553; Assmann, G., Highet, R. J., Sokoloski, E. A. & Brewer, H. B., Jr. (1974) Proc. Nat. Acad. Sci. USA 71, in press; Assmann, G. & Brewer, H. B., Jr. (1974) Proc. Nat. Acad. Sci. USA 71, 989-993] and the identification of conformational amphipathic regions in apoproteins, a new model for human high density lipoproteins is proposed. This model is analogous to membrane models proposed by Singer, in that protein “icebergs” are embedded in a “sea” of lipid.